A COMPARATIVE STUDY OF ZNO NANOPARTICLES OBTAINED IN ELECTRIC DISCHARGE IN THE ABSENCE AND PRESENCE OF ULTRASONIC CAVITATION - Kaptakov, Mikhail; Kohlert, Victoria (Revista Inclusiones, 2020)
In this work, nanoparticles zinc oxides were synthesized in electric discharge in liquid medium in the absence and in presence of ultrasonic cavitation. The size characteristics were studied by electron microscopy and dynamic light scattering techniques. Ultrasound was found to narrow significantly the size distribution width of zinc oxide nanoparticles as well as decrease the average size of nanoparticles. It can be explained by strong ultrasonically induced cavitation effect on the synthesized particles and desagglomeration of particles aggregates.